The Effect of Wordwall-Based Interactive Media through the Team Games Tournament (TGT) Learning Model on Elementary School Students' Interest and Social Studies Learning Outcomes - Ramadhani, Amaliyah; Nursalam, Nursalam; Arifin, Jamaluddin (Journal of Educational Sciences, 2026)
This study aims to examine the effect of Wordwall-based interactive media implemented through the Teams Games Tournament (TGT) learning model on students’ interest and learning outcomes in social studies. The research employed an experimental method with a pretest–posttest control group design. The sample consisted of 42 fourth-grade students from SDN 17 Langnga-Langnga and SDN 39 Tamalalang in Cluster I, Minasatene District, Pangkajene and Islands Regency. Data were collected using questionnaires, observations, achievement tests, and documentation. The data were analyzed using descriptive and inferential statistics with JASP, including normality and homogeneity tests, independent samples t-test, ANOVA, and MANOVA. The results indicated that the implementation of Wordwall-based interactive media through the TGT model had a significant positive effect on students’ interest and learning outcomes. The independent samples t-test showed a significance value of p < .001, indicating differences between the experimental and control groups. Furthermore, MANOVA results (p < .001) confirmed a simultaneous effect on both dependent variables. It can be concluded that the integration of Wordwall and the TGT learning model effectively improves students’ engagement and academic achievement in social studies at the elementary school level.